The Effects of Group Arts Therapy Based on Emotion Management Training on the Emotional Expression, Alexithymia, Depression and Quality of Life in Patients with Schizophrenia - Sang-Yeol Lee; Hye-Jin Lee (BJPsych Open)
Aims: The objective of this study was to investigate the effects of group arts therapy based on emotion management training on emotional expression, positive and negative emotion, alexithymia, depression and quality of life patients with schizophrenia.